Pop music, pop culture - Rojek, Chris (Polity Press, 2011)
What is happening to pop music and pop culture? Synthesizers, samplers and MDI systems have allowed anyone with basic computing skills to make music. Exchange is now automatic and weightless with the result that the High Street record store is dying. MySpace, Twitter and You Tube are now more important publicity venues for new bands than the concert tour routine. Unauthorized consumption in the form of illegal downloading has created a financial crisis in the industry. The old postwar industrial planning model of pop, which centralized control in the hands of major record corporations, and divided the market into neat segments, is dissolving in front of our eyes. This book offers readers a comprehensive guide to understanding pop music today. It provides a clear survey of the field and a description of core concepts. The main theoretical approaches to the analysis of pop are described and critically assessed. The book includes a major investigation of the revolutionary changes in the production, exchange and consumption of pop music that are currently underway.